Crystalline, thermal and swelling properties of starches from single‐segment substitution lines with different Wx alleles in rice (Oryza sativa L.). (13th April 2016) - Teng, Bin; Zhang, Ying; Du, Shiyun; Wu, Jingde; Li, Zefu; Luo, Zhixiang; Yang, Jianbo
Abstract: BACKGROUND: In rice, five common Wx alleles, wx, Wx t, Wx g1, Wx g2 and Wx g3, have been identified according to their apparent amylose content (AAC) phenotypes. Previous studies revealed that this Wx allelic variation may also affect other starch properties. However, so far, to what extent the five Wx alleles influence the crystalline structure, thermal and swelling properties of rice starch is still unclear. For this purpose, a set of single‐segment substitution lines (SSSLs) harboring five different Wx alleles, varying widely in AAC, was used for comparative studies. RESULTS: The crystalline structure, thermal properties and swelling behavior of starches from the SSSLs varied widely depending on Wx genotype. Effects of different Wx alleles on relative crystallinity followed the order wx > Wx t > Wx g1 = Wx g2 > Wx g3 . The glutinous and Wx t genotype starches showed higher gelatinization temperatures and enthalpy compared with other Wx genotypes. The order for swelling power was wx > Wx t > Wx g1 > Wx g2 > Wx g3, while the order for degree of solubility was Wx g3 > Wx g1 > Wx g2 > Wx t = wx . Correlation analysis indicated that AAC was significantly and negatively correlated with relative crystallinity ( r = −0.996, P < 0.01) and swelling power ( r = −0.982, P < 0.01). CONCLUSION: The present results provide new knowledge about the influence of different Wx alleles on the structural and physicochemical properties of rice starch. © 2016 Society of Chemical Industry